The effect of short peptides on the growth and yield of soybeans - T. A. Aseeva; V. Kh. Khavinson; E. S., Mironova; G. A. Ryzhak; N. A., Selezneva; T. N. Fedorova (Юг России: экология, развитие, 2022)
Aim. Study of the effect of short di‐ and tetrapeptides (AB‐0, AE‐0) on the growth, development and productivity of Batya soybean varieties.Material and Methods. Biologically active dipeptide AB‐0 and tetrapeptide AE‐0 were used. Field studies were carried out on meadow‐brown podzolized gley heavy loamy soil. One month before planting, soybean seeds were treated with dipeptide/tetrapeptide of concentrations of 0.01 g/l or 0.001 g/l. Hand‐tended and industrial‐level research was carried out.Results. The use of dipeptide AB‐0 in a hand‐tended study had a positive effect on the growth processes of soybeans of the Batya variety compared to the control. The use of tetrapeptide AE‐0 in a hand‐tended study increased the weight of plants by 7.3‐67.0 g and plant height by 3.0‐9.0 cm compared to the control. The use of dipeptide AB‐0 and tetrapeptide AE‐0 increased the yield of soybeans by a maximum of 81.2‐83.7% compared to the control. The use of peptides AB‐0 and AE‐0 in an industrial‐level experiment increased the yield by 30.5% and 18.4%, respectively, compared with the control.Conclusion. The short peptides AB‐0 and AE‐0 studied had an impact on the growth, development and productivity of Batya soybean varieties. They can be classified as plant growth regulators.